Pengaruh Kualitas Produk, Brand Image, dan WOM Terhadap Keputusan Pembelian Produk Herborist di Kota Batam - Susanto, Fernando; ., Suhardi (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This research aims to determine the influence of product quality, brand image, and word of mouth on the decision to purchase Herborist products. The independent variables studied are product quality, brand image, and word of mouth, while the dependent variable is purchasing decisions. The population of this research is all consumers of PT. Sukses Jaya Indah, Batam, the exact number of which is not known. The sample for this research consisted of 170 respondents using non-probability sampling techniques, namely saturated sampling. Data collection was carried out through distributing questionnaires and data analysis. The results show that product quality has a significant influence on purchasing decisions, brand image has a significant influence on purchasing decisions and word of mouth has a significant influence on purchasing decisions. Apart from that, research shows that product quality, brand image and word of mouth together (simultaneously) have a significant influence on purchasing decisions.